State Regulation on Business Entities Owned by State Universities: Losses and Liability - Hadiyantina, Shinta; Ramadhan, Nandaru (Brawijaya Law Journal, 2019)
The Act of Higher Education stated that Higher Education Management Autonomy is carried out by the basis and objectives and abilities of tertiary institutions. This causes not all State Universities to have the same status, one of which is Legal Entity State University. Legal Entity State University is a state university established by the government which is an autonomous public legal entity. Implementing regulations related to Legal Entity State University is Government Regulation Number 26 in 2015 on the Form and Mechanism of Legal Entity State University Funding. The Government Regulation indicates that Legal Entity State University can have a business entity. The problem is, if the Legal Entity State University carries out a business activity, there will be a possibility that the business will suffer losses. If there is a loss, how is the liability for the loss of the Legal Entity State University?Based on the business judgment rule doctrine, not every business loss is classified as a state loss. If the financial loss is not caused by intentional acts against the law or abuse of authority, then that matter is not classified as a state loss. If the losses included state losses, then the liability losses caused by the activities of those business entities owned by state universities are carried out in three ways, there are criminal liability, civil liability, and accountability in the state administrative law.